Hydrophobic Hydrogels: Hydrophobic Hydrogels with Fruit‐Like Structure and Functions (Adv. Mater. 25/2019). Issue 25 (18th June 2019) - Guo, Hui; Nakajima, Tasuku; Hourdet, Dominique; Marcellan, Alba; Creton, Costantino; Hong, Wei; Kurokawa, Takayuki; Gong, Jian Ping
Abstract : In article number 1900702, Jian Ping Gong and co‐workers discover that hydrophobic networks containing omniphilic organic solvents abnormally swell in water to form hydrophobic hydrogels with high water content (99.6 wt% at most). The hydrophobic hydrogels, having a fruit‐like structure with a semipermeable skin layer and water‐trapped micropores, display unique properties, including enhanced strength, surface hydrophobicity, and antidrying properties, despite their extremely high water content. The abnormal swelling is applied to extract water from saline solution.